Role of marketing in improving didactic activity quality in higher education - GÂRDAN, Adrian Daniel; GEANGU, Iuliana Petronela; ANDRIESEI, Ioana; GICĂ, Ecaterina (Annals of Spiru Haret University. Economic Series, 2016)
Increasing the competence level in teaching services has to be based on a thorough knowledge of both customer needs and the way they are willing to receive the information contents. Applying rigorous scientific marketing principles to the organization and operation of education services offers the fundaments of such a development. The present article outlines the results of a qualitative research – focus group – conducted on a sample of Spiru Haret University students, which had as a main goal identifying the most effective ways of communication in the student-professor relationship in order to design creative teaching materials, perfectly adapted to present educational needs. The conclusions of the research emphasized both the perception of the students regarding the definition of their own position during the education process, and the willingness to actively take part in developing the informational support suitable for educational services. The study also revealed aspects regarding the perception of scientific research, of the willingness to be involved in such a systematic and complex effort.